Pelaksanaan Webinar Makin Cakap Digital sebagai Bentuk Pemberdayaan Pandu Digital Daring untuk Masyarakat Indonesia - Andhi Nur Rahmadi; Nurul Jannah Lailatul Fitria (Journal of Social and Policy Issues, 2022)
The research was conducted on the Makin Cakap Digital Webinar with 5 speakers. One as a key opinion leader is a national public figure named Fanny Fabriana, and 4 resource persons are experts and experts according to the field of discussion, namely Klemens Rahardja, Ninik Rahayu, H. Gatot Sulaeman AP, Msi, and Wanta Heryana. The research in this paper uses descriptive qualitative methods. The research method is based on postpositivism or enterpretive philosophy. To examine the condition of natural objects, where the researcher is the key instrument, the data collection technique is done by triangulation, namely a combination of observation, interviews and documentation. Information and data obtained tend to be qualitative data, data analysis is inductive or qualitative, and qualitative research results are to understand meaning, understand uniqueness, construct phenomena, and find hypotheses. Focus on power-oriented research and new media interventions in the concept of online community empowerment using the webinar platform. Research findings to determine the concept of new media discuss the 4 pillars related to digital literacy held by Kominfo. This webinar program can explain the value of the community to actively participate in the new paradigm of development, especially with regard to digital literacy